2003
DOI: 10.1002/app.13021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of structural changes in thermally enhanced Kevlar‐29 fiber

Abstract: This exploratory investigation examined the structural mechanism accounting for the enhanced compressive properties of heat-treated Kevlar-29 fibers. A novel theory was set forth that hydrogen-bond disruption and concurrent misorientation of crystallites may account for the observed augmentation of compressive properties. To examine the said theory, as-received Kevlar-29 fibers were characterized by thermogravimetric analysis and differential scanning calorimetry in an effort to determine if crosslinking and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
(39 reference statements)
5
41
0
Order By: Relevance
“…Polyethylene terephthalate (PET) is a typical semi-crystalline polymer consisting of spherulites, or crystalline lamellae linked by amorphous tie-chains [10]. Finally, poly(styreneb-ethylene-butylene-b-styrene) (SEBS), a tri-block copolymer commonly used in shoe soles, asphalt, and adhesives [11], adapts a lamellar structure of alternating polystyrene (PS) and poly(ethylene-butylene) (PEB) domains [12].…”
Section: Continuous Dynamic Analysis Of Kevlar and Nomexmentioning
confidence: 99%
“…Polyethylene terephthalate (PET) is a typical semi-crystalline polymer consisting of spherulites, or crystalline lamellae linked by amorphous tie-chains [10]. Finally, poly(styreneb-ethylene-butylene-b-styrene) (SEBS), a tri-block copolymer commonly used in shoe soles, asphalt, and adhesives [11], adapts a lamellar structure of alternating polystyrene (PS) and poly(ethylene-butylene) (PEB) domains [12].…”
Section: Continuous Dynamic Analysis Of Kevlar and Nomexmentioning
confidence: 99%
“…Another type of PPTA fibers, named Twaron  , was produced in 1978 by Teijin Aramid B.V. in Netherland 1,5,[8][9][10][11][12] . Poly (p-phenylene terephthalamide) abbreviated PPTA, are organic fibers acronym originating from aromatic poly (amide) with a distinct chemical composition of wholly aromatic polyamides which at least 85% of amide groups (-CO-NH-) are bond directly to two aromatic rings 2,[12][13][14][15] . Burchill 16 reported that it is largely poly (p-phenylene terephthalamide), Figure 1.…”
Section: Aramid Storymentioning
confidence: 99%
“…They examined the structural mechanism and the mechanical properties of heat treated fibers by means of the thermal and oxidative methods 15,75 .…”
Section: Thermal Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…It reasonably considers to utilize para-aramid fiber which is widely used as protective materials since it has high modulus, strong strength and the flame retardance. There are many inter-chain bonds and these strong intermolecular hydrogen bondings interaction between the carbonyl groups and NH centers make the aramid fiber have a high crystallinity [14,15,16]. Therefore, it is difficulty to dissolve using common solvent.…”
Section: Introductionmentioning
confidence: 99%